KARAKTERISTIK PENGOLAHAN LIMBAH CAIR PABRIK MINYAK KELAPA SAWIT DALAM BIOREAKTOR CIGAR SEMI KONTINU - Shintawati, Shintawati; Hasanudin, Udin; Haryanto, Agus (The University of Lampung, 2017)
Palm oil mill effluent (POME) waste water contains high consentration of organic pollutants. Anaerobic treatment is suitable to reduce the pollutans and also produce methane as one of renewable energy sources. Anaerobic degradation is complicated and sensitive process to the environtment, such as temperature and organic consentration. This study aims to determine characteristic of palm oil mill waste water treatment using semicontinue anaerobic CIGAR bioreactor. The seed was collected from sludge of anaerobic pond at POME treatment facility of PTPN VII Bekri. The substrat used in this experiment was fresh POME from the same mill. Initially, 4,375m3 of sludge was introduced into the bioreactor. The seed was acclimatized at a loading rate of 50 l/day for about a week. Anaerobic treatment was conducted at room temperature and the substrat was fed semicontinuelly at a loading rate of 100 to 350 liter/day. Results showed, that the stability of anaerobic degradation was achieved at an organic loading rate (OLR) of 0,9-3,11 kg/m3/day with COD removal more than 90% and maximum biogas production of 2,59 m3/day.Â Keywords : palm oil mill effluent, anaerobic bioreactor, COD removal, biogas.